2003
DOI: 10.1021/jf021049m
|View full text |Cite
|
Sign up to set email alerts
|

6β-Hydroxygedunin from Azadirachta indica. Its Potentiation Effects with Some Non-azadirachtin Limonoids in Neem against Lepidopteran Larvae

Abstract: The biological activity of 6beta-hydroxygedunin isolated from Azadirachta indica A. Juss. was assessed using the gram pod borer, Helicoverpa armigera (Hubner), and Asian armyworm, Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae), alone and in combination with other limonoids, gedunin, salannin, nimbinene, and azadirachtin. The compound exhibited growth inhibitory activity in artificial diet bioassays, with 24.2 and 21.5 ppm, respectively, inhibiting growth by 50%. This efficacy was higher in comparison t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 21 publications
1
27
0
2
Order By: Relevance
“…3,23,24) Azadirachtin and related limonoids from neem tree have shown strong antifeedant and growth regulating activity and at the same time these compounds are highly bio-degradable, are very slightly toxic towards non-target organisms, while they are non-toxic towards humans and mammals in general, with very low persistence in systemic action, 21,25) this is the reason why an array of insecticides and pesticides comprising of azadirachtin as principal constituent and based on neem extract are available today in the market. Koul et al 26,27) have further shown that azadirachtin being the most active compound in neem is not synergized or influenced by any other limonoid, but other non-azadirachtin limonoids show synergism in specific combination, which may be due to their different modes of action.…”
Section: Activities On Insectsmentioning
confidence: 99%
“…3,23,24) Azadirachtin and related limonoids from neem tree have shown strong antifeedant and growth regulating activity and at the same time these compounds are highly bio-degradable, are very slightly toxic towards non-target organisms, while they are non-toxic towards humans and mammals in general, with very low persistence in systemic action, 21,25) this is the reason why an array of insecticides and pesticides comprising of azadirachtin as principal constituent and based on neem extract are available today in the market. Koul et al 26,27) have further shown that azadirachtin being the most active compound in neem is not synergized or influenced by any other limonoid, but other non-azadirachtin limonoids show synergism in specific combination, which may be due to their different modes of action.…”
Section: Activities On Insectsmentioning
confidence: 99%
“…Phytochemicals have shown different kinds of actions that can modify specific physiological processes in insects (Liu et al, 2007). Koul et al (2003) noticed that plant chemicals' defense against insect herbivory almost never depends on a single compound, but instead several compounds interact with pests, individually or in unison. Application of biopesticides has been reported to have positive impacts on bollworm population management (Ge and Ding, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Epoxyazadiradione, 17-epiazadiradione, and nimbin were not active. 6β-Hydroxygedunin, isolated from Azadira chta indica , exhibited growth inhibitory activity in feeding bioassays against gram pod borer, Helicoverpa armigera , and Asian armyworm, Spodoptera litura , with EC 50 of 24.2 and 21.5 ppm, respectively (Koul et al 2003 ). Its efficacy was higher in comparison to gedunin (EC 50 = 50.8 and 40.4 ppm), salannin (EC 50 = 74.5 and 72.0 ppm) and nimbinene (EC 50 = 391.4 and 404.5 ppm).…”
Section: Other Usesmentioning
confidence: 99%